Mortgages denominated in domestic and foreign currencies: Simple models - Júlia Király; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2015)
After the short temporary popularity of foreign currency denominated (FXD) loans, during the Great Financial and Economic Recession (2007- 2013), the burden of these loans has become unaffordable for a lot of borrowers in East Central Europe. We have designed a family of simple models to compare the cash flows of installments and the paths of outstanding debts denominated in domestic and foreign currencies, respectively. Having these models, we are able to draw several conclusions relevant to the recent debates about the FXD loans. Our study demonstrates the key role played by the uncovered interest rate parity in the comparisons. Moreover, we give a closed-form solution for the trade-off between the depreciation and the unilateral FX interest rate increases by the banks. Adding a lifetime utility function to our simple model, we determine the optimal size for domestic and foreign currency denominated loans, respectively.
Keywords: C63; D14; G21; 330; mortgage; currency denominated loan; credit crisis; payback models with annuity